1997
DOI: 10.1023/a:1005916627972
|View full text |Cite
|
Sign up to set email alerts
|

Animal models of breast cancer: experimental design and their use in nutrition and psychosocial research

Abstract: This is the second Special Issue addressing the diversity and use of animal models of breast cancer. The previous issue (Breast Cancer Res Treat 39:1-135, 1996), dealt with a variety of topics such as the characteristics of chemically- and virally-induced rodent models, immunobiologies of immunedeficient mice, transgenic mouse models, and models of metastasis. In the first part of this second Special Issue, the articles address animal models for studying life-style factors, including psychosocial, exercise, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
6

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 68 publications
0
11
0
6
Order By: Relevance
“…Because T␣1 prevented mammary cancer in both animal models of mammary cancer, it is a chemopreventive agent regardless of estrogen receptor status. 36 Previously, it was found that retinoic acid, which increases TGF-␤ expression, increased survival of C3(1)SV40T antigen mice significantly from 20 to 23 weeks and reduced tumor burden by 67%. 37 VIP hybrid, which is a VIP receptor antagonist, increased survival of C3(1)SV40T antigen mice by 2 weeks and reduced the tumor burden by 50%.…”
Section: Breast Carcinogenesismentioning
confidence: 98%
See 1 more Smart Citation
“…Because T␣1 prevented mammary cancer in both animal models of mammary cancer, it is a chemopreventive agent regardless of estrogen receptor status. 36 Previously, it was found that retinoic acid, which increases TGF-␤ expression, increased survival of C3(1)SV40T antigen mice significantly from 20 to 23 weeks and reduced tumor burden by 67%. 37 VIP hybrid, which is a VIP receptor antagonist, increased survival of C3(1)SV40T antigen mice by 2 weeks and reduced the tumor burden by 50%.…”
Section: Breast Carcinogenesismentioning
confidence: 98%
“…Estrogen receptors are not abundant in C3(1)SV40T antigen mice, however, they are present in the Fisher rat. Because Tα1 prevented mammary cancer in both animal models of mammary cancer, it is a chemopreventive agent regardless of estrogen receptor status 36 . Previously, it was found that retinoic acid, which increases TGF‐β expression, increased survival of C3(1)SV40T antigen mice significantly from 20 to 23 weeks and reduced tumor burden by 67% 37 .…”
Section: Breast Carcinogenesismentioning
confidence: 99%
“…There are many strains of genetically determined immunodeficient mice containing single mutations (e.g., nude, scid, beige, xid, rag-1 null, rag-2 null) or combined mutations, (e.g., bg/nu, bg/nu/xid, nude/scid, nod/scid) available for cancer research [1618]. These strains have different immunological impairment and the availability of more permissive mouse strains can strongly increase the efficiency of xenotransplantation; however severely immunocompromised mice also have a higher cost and their manipulation can be extremely demanding requiring controlled husbandry environment and highly trained personnel.…”
Section: Mouse Preclinical Cancer Modelsmentioning
confidence: 99%
“…Chromosome 6 hybrids engin-279 eered to express green fluorescent protein were used 280 to demonstrate that they completed every step of the 281 metastatic cascade except proliferation at the second-282 ary site [67]. Using subtractive hybridization the 283 KISS-1 metastasis suppressor was identified [68]. 284 Also using the C8161 melanoma, MMCT of chromo-285 some 1 suppressed metastasis [69].…”
Section: Stochastic and Selective Aspects Of Cancer Metastasismentioning
confidence: 99%